Comparação da eficiência de hidrólise enzimática de bagaço de cana pré-tratado entre três formas de operação em batelada - Cappellazzo, Mirella (2009)
In this study, the efficiency of three operation forms of the batch reactor for the enzymatic hydrolysis of steam-exploded and washed sugarcane bagasse, aiming for glucose production, were evaluated. A "fed-batch" reactor and a consecutive batches reactor where the hydrolysate was used for enzyme adsorption were compared to the conventional batch reactor. In the "fed-batch" reactor, the total solids loading was split into fractions, which were added at different intervals, during the total hydrolysis time, without removing non-hydrolyzed waste. In the consecutive batches reactor, after a determinate reaction time, the hydrolysate was separated and put together with a new portion of fresh pre-treated bagasse, intending for enzyme readsorption. The bagasse in suspension in the hydrolysate, containing the enzyme adsorbed, was then separated from the sugar solution by vacuum filtration and after, submitted to a new hydrolysis batch, without more enzyme addition. The comparison was made in terms of glucose production, which can be converted into ethanol. An enzyme system comprising cellulases and cellobiase produced by Trichoderma reesei Rut-C30 and Aspergillus awamori, was used in the enzymatic hydrolysis. The saccharification rate was higher in the first 24 hours, within more than half of the glucose was produced. The alternative reactors to the conventional batch reactor were tested motivated by the premise that their operation forms would cause minor inhibition of the hydrolysis reaction, by the gradual feeding of the substrate and separation of the produced syrup from the non reacted solid waste, consequently reaching a larger gain in glucose production, for the same reaction time. Nevertheless, the conventional batch reactor was more efficient than the "fed batch" and consecutive batches reactors, attaining a larger glucose production, in the tested conditions.